Application of Mono-Diacylglycerol from Fully Hydrogenated Palm Kernel Oil for making Ice Cream - mursalin mursalin (Jurnal Teknologi & Industri Hasil Pertanian, 2020)
The quality of ice cream is largely determined by the type of emulsifier used.  The utilization of an appropriate emulsifier will produce ice cream with good quality. A mixture of Mono-Diacylglycerol made from fully Hydrogenated Palm Kernel Oil (furthermore in this paper we named it as MDAG) and Tween-80 in various comparisons was used as an emulsifier in ice cream making and their effects were analyzed. The composition of the mixture was determined based on 5 types of HLB values, namely 4.5 (E1); 5.3 (E2); 6.1 (E3); 6.9 (E4); and 7.7 (E5); obtained from a mixture of MDAG and Tween-80 (87.5: 12.5); (80.8: 19.2); (74.2: 25.8); (67.5: 32.5); and (60.8: 39.2), respectively. The five treatment levels of the mixture composition of the two types of emulsifiers were arranged in a completely randomized design with 4 replications. The parameters observed were overrun, melting time, texture, and consumer preferences for taste and overall acceptance. The data obtained were statistically analyzed using ANOVA, followed by Duncan New Multiple Range Test (DNMRT) . The results showed that the composition of the mixture of MDAG and Tween-80 had a very significant effect on overrun, melting time, texture, taste, and overall acceptance of the ice cream produced. The best quality ice cream was obtained from the mixture composition of MDAG and Tween-80 at HLB 6.1 with MDAG: Tween-80 (74.2: 25.8) with an overrun value of 68.43%, melting time of 21.13 minutes, texture score of 4.76 (as good as a local commercial ice cream produced in Kumpeh District, Muaro Jambi), preferences score of taste was 5.92 (from a score interval of 1-7), and an overall acceptance score was 5.56 (from a score interval of 1-7).